Cluster endophthalmitis due to Stenotrophomonas maltophilia following intravitreal bevacizumab: outcomes of patients from North India. Issue 9 (12th November 2018) - Agarwal, Aniruddha Kishandutt; Aggarwal, Kanika; Samanta, Ramanuj; Angrup, Archana; Biswal, Manisha; Ray, Pallab; Dogra, Mohit; Katoch, Deeksha; Bansal, Reema; Singh, Ramandeep; Dogra, Mangat R; Gupta, Vishali
Abstract : Purpose: To study features, management and outcomes of cluster endophthalmitis following intravitreal bevacizumab (BCZ) injection in North India. Methods: In this retrospective study, 28 patients (23 men) (mean age of 59.07±13 years) who received intravitreal injection of BCZ were included. Demographic details, best corrected visual acuity (BCVA), clinical features, microbiological findings and management of patients who developed endophthalmitis after injection of contaminated BCZ injections were reviewed. The organism isolated was Stenotrophomonas maltophilia . Results: All patients suffered from painful diminution of vision within 24–48 hours. Of the 28 eyes, 12 had lid and corneal oedema, raised intraocular pressure (IOP) (difference between mean preinjection and postinjection IOP: 4.42 mm Hg; p=0.005) and toxic anterior segment syndrome-like picture. 16 eyes presented with clear cornea, severe vitritis and poor media clarity. Among these, three eyes showed posterior hypopyon. Seventeen eyes underwent primary pars plana vitrectomy (PPV) and intravitreal vancomycin+ceftazidime based on severity of inflammation. Eleven eyes underwent primary tap and inject. Among these, four eyes required PPV due to persistent inflammation. Eleven eyes showed positive staining for Gram-negative bacilli. Seven eyes were culture positive for S. maltophilia . Mean preinjection BCVA was 0.77±0.48. The first recorded postinjection BCVA was 2.52±0.82. BCVA (at 1 month) improved to 0.88±0.66. Conclusions: S. maltophilia can be found contaminating hospital surfaces and water supply. Early PPV, prompt intravitreal antibiotics and close communication with microbiologists greatly aided in salvaging all eyes from our cohort. Majority of the patients recovered their preinjection BCVA and IOP and achieved quiescence of inflammation.